Menjelajahi Keterlibatan Mahasiswa dan Pergaulan Bebas di Kalangan Mahasiswa - Nabilah, Dewi Irsanti; Maryam, Effy Wardati (Inquest Journal, 2024)
This correlational quantitative study investigates the relationship between student engagement and social loafing among university students. Using a sample of 336 students selected through proportional stratified random sampling, the study employed Likert scale instruments to measure social loafing and student engagement. Data analysis conducted with SPSS Version 25 revealed a significant negative correlation between student engagement and social loafing, indicating that higher levels of student engagement correspond to lower instances of social loafing during learning activities. These findings underscore the importance of fostering active student participation to mitigate social loafing tendencies, offering practical insights for enhancing classroom learning dynamics